Associação entre o estado nutricional e a reação hansênica - um coorte de portadores de hanseníase em municípios da Grande Vitória (ES) - Montenegro, Rosa Maria Natalli (2010)
Introduction. Leprosy is still considered a public health problem in Brazil and in the world. Its complications, known as leprosy reactions, are severe inflammatory manifestations that occur during the chronic course of the disease which may lead to permanent damages. It`s important to identify the involved risk factors so that it`s possible to observe the patients who are most at risk from this disease, this way trying to avoid serious sequels. Objectives. To delineate the nutritional profile of the patients who suffer from leprosy; to relate the association between the nutritional status and the appearing of the leprosy reaction taking a sample of 152 and 141 patients respectively. Methodology. A longitudinal study from January to December 2009 of affected leprosy patients who were treated for at least 6 months in the initial polichemiotherapic treatment or until the evidence of the leprosy reaction. The data which were collected from the Health Center in Grande Vitória, included sociodemographic, antrometric, biochemical and nutritional aspects through a questionnaire about eating frequency (EFQ) which was validated and also adapted. The Body Mass Index (BMI) was calculated for the nutritional status evaluation. Results. This study has shown that 79(52%) of the participants were of the female sex, the average age was 40.4(about 16.9); 81(53.3%) were hired on; the average period of study was 7,1 (about 4.5). In relation to the disease, 79(52%) presented multibacilli and 73(48%) paucibacilli. The bacillus rate was negative in 125(82.2%) patients. The overweight aspect was identified in 11.8% and 5.3 presented underweight. The most consumed foods were rice and beans, 87.3% and 88.7 respectively. The leprosy reaction has occurred mostly in a dimorfa way (17 patients, 47.2%) and virchoviana (8 patients, 8.3%) (p=0,0023), in relation to the association of the nutritional status and the appearing of the leprosy reaction, when the classification of the Body Mass Index is used, the reaction occurs in 18(50%0 (p=0,3836) in eutrophic patients. Considering the arm circumference measurement (AC), the leprosy reaction also appears more frequently among the eutrophics, 26 patients(72.2%); p=0,1679. In the tricipal skin-pleat, the overweight category and obesity represent 19 patients (52.8%) of the leprosy reactions (p=0,0906) and by using the arm muscle circumference (AMC), the reaction occurrence is in 25 patients (69.4%) among the eutrophics (p=0,9222). Conclusion. Knowing the nutritional profile of the infectious disease patients like Hansen`s disease may be important to a more appropriate treatment for them as well as to provide relevant hints for a more efficient intervention in order to improve their like quality. The results from this study don`t show association between the nutritional status and the leprosy reaction. Thus, new studies are considered necessary with a greater number of patients especially the ones who present evidences of leprosy reaction, trying to prove the findings.